Simulated paraplegia: an occasional problem for the neurosurgeon. Issue 8 (August 1985) - Maurice-Williams, R S; Marsh, H
Abstract : Fourteen cases of simulated paraplegia and tetraplegia encountered amongst 4, 800 neurosurgical admissions are described. The classification of such cases is difficult. Use of the term "hysteria" depends on whether the behaviour is judged to be conscious or not, but this can rarely be decided. In most of the patients the paralysis was of relatively short duration and recovered rapidly with simple methods of treatment which permitted this to occur without loss of face, but such cases presenting as acute neurological emergencies represent only one relatively simple form of pretended or "hysterical" illness. Many of these patients are probably never seen by psychiatrists.